Minimally Interrupted Non-Vitamin K Antagonist Oral Anticoagulants vs. Bridging Therapy and Uninterrupted Vitamin K Antagonists During Atrial Fibrillation Ablation: A Retrospective Single-Center Study - Tang, Lihong; Liu, Haiyan; Deng, Hai; Zhan, Xianzhang; Fang, Xianhong; Liao, Hongtao; Liu, Yang; Fu, Lu; Fu, Zuyi; Liu, Huiyi; Wu, Shulin; Xue, Yumei (Frontiers in Medicine, 2020)
Objectives Although the latest international guidelines recommend the use of uninterrupted non-vitamin K antagonist oral anticoagulants (NOAC) during atrial fibrillation (AF) ablation, it does not reflect current clinical practice as most centers still use a minimally interrupted NOAC strategy. The purpose of this study was to evaluate the safety and effectiveness of minimally interrupted NOAC compared with bridging therapy and uninterrupted vitamin K antagonist (VKA) for non-valvular AF ablation. Methods A total of 4520 patients who underwent AF ablation between January 2010 and December 2018 were included in the analysis. According to their peri-procedural anticoagulation strategies, patients were divided into 3 groups: Bridging heparin group (n=1848); Uninterrupted VKA group (n=796) and Minimally interrupted NOAC group (Total n=1876; dabigatran: n=865; rivaroxaban, n=1011). A combined complication endpoint (CCE) as composed of any bleeding complications and thromboembolic events was analyzed. Results Rates of thromboembolisms were similar among the 3 groups (0.22% for Bridging heparin group, 0.25% for Uninterrupted VKA group and 0.11% for Minimally interrupted NOAC group, p=0.626). There was significant difference among the 3 groups for the incidence of overall bleeding events (8.50% for Bridging heparin group, 4.52% for Uninterrupted VKA group and 2.67% for Minimally interrupted NOAC group, p<0.001). A significant difference of CCE rates was shown in the Minimally interrupted NOAC group as compared with the Uninterrupted VKA group (2.77% vs. 4.77%, p=0.008) and the Bridging heparin group (2.77% vs. 8.71%, p<0.001). There was no significant difference in CCE rates among the different NOACs (dabigatran 2.9% vs. rivaroxaban 2.7%, p=0.773). Conclusions In patients undergoing AF ablation, minimally interrupted NOACs during the peri-procedural period appears safer and equally effective when compared to the bridging heparin and uninterrupted VKA therapy.